2022
DOI: 10.3389/fphar.2022.828513
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment of Secondary Lymphedema

Abstract: Lymphedema is a chronic disease that results in swelling and decreased function due to abnormal lymphatic fluid clearance and chronic inflammation. In Western countries, lymphedema most commonly develops following an iatrogenic injury to the lymphatic system during cancer treatment. It is estimated that as many as 10 million patients suffer from lymphedema in the United States alone. Current treatments for lymphedema are palliative in nature, relying on compression garments and physical therapy to decrease int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 162 publications
(168 reference statements)
0
17
0
Order By: Relevance
“…26,27 However, the application of VEGF-C therapy in the clinical setting has yet to be realized because VEGF-C acts as a key regulator of the tumor microenvironment, potentially increasing the risk of recurrence and metastasis. 25,28 Previous studies have reported that Roxadustat is noncarcinogenic 29 and it was found not to promote the initiation, progression, or metastasis of tumors in a VEGF-sensitive spontaneous breast cancer model. 30 Meanwhile, a phase 2 study is being conducted to evaluate roxadustat for the treatment of anemia in patients receiving chemotherapy for nonmyeloid malignancies (NCT04076943).…”
Section: Hif-1α Promotes Lymphangiogenesis By Inducing Vegfr-3 and Ve...mentioning
confidence: 99%
“…26,27 However, the application of VEGF-C therapy in the clinical setting has yet to be realized because VEGF-C acts as a key regulator of the tumor microenvironment, potentially increasing the risk of recurrence and metastasis. 25,28 Previous studies have reported that Roxadustat is noncarcinogenic 29 and it was found not to promote the initiation, progression, or metastasis of tumors in a VEGF-sensitive spontaneous breast cancer model. 30 Meanwhile, a phase 2 study is being conducted to evaluate roxadustat for the treatment of anemia in patients receiving chemotherapy for nonmyeloid malignancies (NCT04076943).…”
Section: Hif-1α Promotes Lymphangiogenesis By Inducing Vegfr-3 and Ve...mentioning
confidence: 99%
“…Lymphedema is caused by a dysfunction of the lymphatic system, resulting in localized interstitial fluid retention and tissue swelling; it is classified as primary or secondary. Primary lymphedema develops due to inherited hypoplasia/dysplasia or dysfunction of lymphatic vessels because of some intrinsic factors such as genetic mutations in the signaling pathway for vascular endothelial growth factor C (VEGF-C), while secondary lymphedema is caused by a dysfunction of the lymphatic vascular system due to trauma or parasitic infection [ 1 , 2 , 3 ]. Although the incidence of secondary lymphedema has been declining due to advances in surgery, this iatrogenic disorder has a strong negative impact on physical and mental quality of life (QOL) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, radiation therapy (RT) increases the risk of lymphedema in the upper and lower limbs; for instance, in breast cancer patients, the risk of lymphedema is five times higher with postoperative RT than with axillary lymph node dissection alone [ 5 ]. Patients with lymphedema typically present with symptoms such as altered mechanical properties and sensitivity of the skin, increased susceptibility to systemic and local infections, decreased function of the affected upper or lower limb, and chronic pain and discomfort [ 3 , 6 ]. In addition, patients may have problems with body image and social acceptability and exhibit low self-esteem [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive growth of lymphatic vessels (lymphangiogenesis) is associated with transplant rejection and cancer ( Vaahtomeri et al, 2017 ; Morfoisse and Noel, 2019 ). Failure of the lymphatic system leads to an impaired drainage capacity resulting in fluid accumulation and tissue swelling called lymphedema (LD) ( Grada and Phillips, 2017 ; Dayan et al, 2018 ; Azhar et al, 2020 ; Brown et al, 2022 ). LD is a chronic, multifactorial disease affecting approximately 250 million people worldwide ( Oliver et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This lifelong and unpredictable condition often develops in a delayed manner, months or even years after surgery. Current treatments are poorly effective, mainly palliative and include compression massage, extensive decongestive therapy by physiotherapists, restrictive diets or surgery to transfer vascularized lymph nodes ( Carl et al, 2017 ; Borman, 2018 ; Chang et al, 2021 ; Brown et al, 2022 ). Pharmacological treatments based on pro-lymphangiogenic factors (VEGF-C) are promising, but are not sufficient to restore functional lymphatic vessels with efficient valves ( Szoke et al, 2021 ; Brown et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%